213k views
4 votes
Exercise 8.5.1: Proving divisibility results by induction. About Prove each of the following statements using mathematical induction. (a) Prove that for any positive integer n, 4 evenly divides 32n-1. (b) Prove that for any positive integer n, 6 evenly divides 7n - 1.

User Kosh
by
5.1k points

1 Answer

3 votes

Answer:

a) 4(9
x+2)

b)6(7
x +1)

Explanation:

a) Prove that for any positive integer n, 4 evenly divides 32n-1

checking whether the statement is correct or not

∴ n = 1;

=
3^(2n) -1

=
3^(2*1) -1

= 9 - 1

= 8

hence it is divisible by 4

Let the statement is for n = k


3^(2k ) -1 = 4
x(equation 1)


(3^(2))^(k) -1 = 4
x


9^(k) -1 = 4
x (equation 1)

Now, we have to proof the statement is true for n = k+1

=
3^(2(k+1)) -1

=
(3^(2k) * 3^(2) ) -1 (
x^(a+b) = x^(a) * x^(b))

Adding & Subtracting 8

=
(3^(2k) * 3^(2) ) -1 +8 -8

=
9^(k) * 9 -9 + 8

taking common 9

= 9(
9^(k) -1)+8

= 9 (4
x) +8 (from equation 1)

= 36
x + 8

= 4(9
x+2)

if (9
x+2) = p

then = 4p

Since
3^(2(k+1)) -1 = 4p evenly divisible by 4

therefore given statement is true

b)Prove that for any positive integer n, 6 evenly divides
7^(n) - 1

checking whether the statement is correct or not

∴ n = 1;


7^(n) - 1

7 - 1

6

6 is divisible by 6

hence the given statement is true for n = 1

let it also true for n = k


7^(k) - 1 = 6x (equation 2)

Now we have to proof the statement is true for n = k+1


7^(k+1) - 1


7^(k)*7 - 1

Adding & Subtracting 6


7^(k)*7 - 1 +6 - 6


7^(k)*7 - 7 +6


7(7^(k)* - 1) +6

7(6
x )+6 ( from equation 2)

= 42
x + 6

= 6(7
x +1)

if 6(7
x +1) = p

then = 6p

Since
7^(k+1) -1 = 6p evenly divisible by 6

therefore given statement is true

User Piotr Babij
by
4.9k points